The Role Of The Police In Law Enforcement Of Drug Circulation Among Students - Bakti Kautsar Ali (Jurnal Hukum Khaira Ummah, 2021)
The purpose of this paper is to identify and analyze the role and constraints of the Cilacap Resort Police in dealing with narcotics abuse crimes committed by students in the Cilacap Regency area. The research method used is empirical juridical. The results of this study are the role of the police in overcoming narcotics among adolescents, namely eradicating and tackling narcotics abuse, providing socialization and guidance to the community, patrol around a place that is suspected to be a place of sale and a place that is often used for drug parties, in collaboration with community organizations, in collaboration with educational institutions and religious institutions. Constraints experienced by the police are the lack of field coordination and limited personnel during operations, lack of coordination with institutions and agencies in the prevention and eradication process, the presence of law enforcement officers who leak information during raids, lack of funds in terms of making arrests and providing counseling to the public.